KESENJANGAN LAYANAN HUBUNGAN PENJUAL DAN PEMBELI DALAM SUPPLY CHAIN MANAJEMEN (SCM) DAN DAMPAKNYA PADA PENGEMBANGAN AGRIBISNIS KENTANG DI PROVINSI NAD - Suyanti Kasimin (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
Service Gaps relationship of Sellers and Buyers in Supply Chain Management (SCM) and its Impacts on Acehs Potatoes AgribusinessABSTRACT. The purpose of this study is to analyze the fulfillment of services between potato agribusiness developments actors in Aceh. By using Supply Chain Management in Buyer-Seller Relationship, the results showed that there were three measurements of success between the actors in the Aceh Province. Those were: the level of satisfaction, the level of trust and the level of dependency. The analysis showed that the satisfaction of downstream actors (district merchants and retailers) was greater than the upstream actors (potato farmers and traders). Upstream offender was in a weak position shown by the trust and the high dependence on downstream actors. Traders and merchants across the city experienced the level of trust, satisfaction and a low dependency. The result indicated development of potato agribusiness was slow and was not dominant as a source of farmers income.